Cutaneous Adverse Drug Reaction due to Anti-TB Drug Allergy in TB-HIV Patient: A Case Report - Yanifitri , Dewi Behtri; Arliny, Yunita; Hayati, Rahmi (Indonesian Society of Respirology (ISR), 2025)
Background: In people living with HIV/AIDS (PLHIV), tuberculosis (TB) is the leading cause of death, with a 20 times higher risk of developing active TB compared to people without HIV. PLHIV are also at higher risk of experiencing cutaneous adverse drug reactions (CADR) caused by anti-TB drugs. The delayed therapy of TB caused by CADR might make TB management more difficult. Case: A 23-year-old male with clinically confirmed pulmonary TB on intensive phase anti-TB therapy experienced erythroderma due to allergies to anti-TB drugs and stage III HIV. In the drug challenge, it was found that the patient showed an allergic reaction in the form of a reddish rash that spread widely on the anterior and posterior thorax and abdomen after consuming rifampicin and pyrazinamide. Discussion: The patient's treatment was then added with cetirizine and methylprednisolone. The anti-TB drugs will be given for 9 months, with the intensive phase of 2 months, and the continuation phase of 7 months. Conclusion: There is a very high risk of CADR in TB patients with HIV infection. Monitoring the side effects of anti-TB regularly and identifying immediately which anti-TB drug causes the allergy is significant as the key to managing CADR in TB-HIV patients. Anti-TB drug provocation tests for each drug and a gradual dose increase are carried out if the clinical CADR has disappeared or improved.